2015
DOI: 10.15537/smj.2015.1.9141
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of abnormal Papanicolaou smear in Central Saudi Arabia

Abstract: Objectives:To assess the prevalence and characteristics of abnormal pap smear in the central region of Saudi Arabia.Methods:In this retrospective case control study conducted in the Departments of Obstetrics and Gynecology, and Histopathology at King Abdulaziz Medical City, Riyadh, Kingdom of Saudi Arabia, all pap smears screened for Saudi women between 2008 and 2011 were reviewed. Approximately 5000 pap smears are screened annually at King Abdulaziz Medical City utilizing the Bethesda III System (2001). All a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 22 publications
5
18
1
Order By: Relevance
“…In our study, ASCUS was seen in only 6 smears (16.2%) of the epithelial lesions, while LSIL and HSIL were the most frequent lesions, accounting for 36.8% of the total cases for each. In most Saudi studies, ASCUS represented the most common finding (Al-Kadri et al, 2015 andAltaf andMufti, 2012). Similar studies from United Arab Emirates (UAE) and Turkey reported that ASCUS was the most common category (Alzaabi and Al Muqbali, 2015;Korkmaz and Gencer, 2014).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…In our study, ASCUS was seen in only 6 smears (16.2%) of the epithelial lesions, while LSIL and HSIL were the most frequent lesions, accounting for 36.8% of the total cases for each. In most Saudi studies, ASCUS represented the most common finding (Al-Kadri et al, 2015 andAltaf andMufti, 2012). Similar studies from United Arab Emirates (UAE) and Turkey reported that ASCUS was the most common category (Alzaabi and Al Muqbali, 2015;Korkmaz and Gencer, 2014).…”
Section: Discussionmentioning
confidence: 83%
“…The prevalence of ECL in the present study was 2.4%, which is one of the lowest rates of prevalence in KSA, Gulf Cooperation Council (GCC) countries, and other countries. Previous studies from different areas in KSA showed ECL prevalence rates ranging from 1.7% to 17.2% (Al-Kadri et al, 2015;Jamal and Al-Maghrabi, 2003;Al-Jaroudi andHussain, 2010 andAltaf andMufti, 2012). Regarding GCC countries, the largest study was carried in Kuwait with an evaluation of 140,404 smears throughout 21 years in which the reported prevalence rate of ECL was 4.3% (Table 4) (Kapila et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Presence of abnormal cervical appearance was associated with increased epithelial cell abnormalities. Squamous cell abnormalities were identified in 767 out of 841 (91%) of studied patient, and the cervical glandular epithelial abnormalities were appeared in 74 out of 841 (9%) of patients [6]. The patients with early invasive cervical cancer are asymptomatic and the cervical malignant changes not visible clinically and can be detected only during routine cervical cytological screening.…”
Section: Introductionmentioning
confidence: 94%